Where Are the Snows : Poems - Rooney, Kathleen, 1980- (Book collections on Project MUSE., 2022)
"Where Are the Snows takes its title from the famous refrain of François Villon's 15th century poem 'Ballad of the Ladies of Times Past.' Like that poem, the book functions, among other things, as an ubi sunt, Latin for 'Where are they?' as in 'Where are the ones who came before us?' -- the beautiful, the strong, the virtuous, all of them? In keeping with that long tradition, these poems offer a way to think about life's transience, its beauty, its absurdity, and of course its mortality. Allusive and associative, anti-capitalist and unapologetically political, aligned somewhere between comedy and anger, this poetry juxtaposes the triumphs and tragedies (mostly tragedies) of our current age with those of history, and-by wondering 'Where are they?'-explores the questions of where we are now and where we might be going"--